2020
DOI: 10.1177/2040622320961617
|View full text |Cite
|
Sign up to set email alerts
|

COPD smokers who switched to e-cigarettes: health outcomes at 5-year follow up

Abstract: Background and Aims: The long-term health effects of the use of electronic cigarettes (ECs) in patients with chronic obstructive pulmonary disease (COPD) are largely unexplored. We present findings from a 5-year prospective assessment of respiratory parameters in a cohort of COPD patients who substantially reduced conventional smoking or achieved abstinence by switching to ECs. Methods: Patients were evaluated prospectively for their measurements of respiratory exacerbations, spirometric indices, quality of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 58 publications
4
54
0
2
Order By: Relevance
“…Moreover, similar findings have been also reported in COPD patients using another class of combustion-free nicotine delivery products (i.e. e-cigarettes) [ 18 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, similar findings have been also reported in COPD patients using another class of combustion-free nicotine delivery products (i.e. e-cigarettes) [ 18 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, similar findings have been also reported in COPD patients using another class of combustion-free nicotine delivery products (i.e. e-cigarettes) [18,26,27]. Nearly 60% of COPD patients using HTPs abstained completely from cigarette smoking throughout the duration of the study, whereas those continuing to smoke (dual users) showed a consistent decline in their daily cigarette consumption from the baseline of at least 70% at all study visits.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A five year follow-up clinical study (assessments at 12, 24, 48, and 60 months) of patients with COPD compared 19 patients who completely or partially substituted ENDS for smoking to 20 controls who smoked [38]. Switching to ENDS contributed to a rapid improvement in cardiorespiratory health, with better quality of life, improved exercise tolerance, and an approximately 50% reduction in COPD exacerbations.…”
Section: Methodsmentioning
confidence: 99%
“…A 5-year follow-up clinical study (assessments at 12, 24, 48, and 60 months) of patients with COPD compared 19 patients who completely or partially substituted ENDS for smoking to 20 controls who smoked [ 38 ]. Switching to ENDS contributed to a rapid improvement in cardiorespiratory health, with better quality of life, improved exercise tolerance, and an approximately 50% reduction in COPD exacerbations.…”
Section: Omitted From the Terms Of Reference: Tobacco Harm Reductionmentioning
confidence: 99%